2020
DOI: 10.3389/fneur.2019.01410
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Traumatic Brain Injury and Hypothalamic-Pituitary Disorders in Arizona

Abstract: hypothalamic-pituitary disorder after a TBI in the pediatric population. Our results contribute to a body of knowledge demonstrating a TBI etiology for idiopathic endocrine disorders, and thus advise physicians with regard to TBI follow-up care that includes preventive screening for endocrine disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
1
17
0
1
Order By: Relevance
“…In juvenile and aging TBI research, women and female rodents would not be actively cycling, thereby having lower circulating gonadal hormones levels, where post-menopausal women have been indicated to respond similar to males (78). However, an epidemiological study of TBI in pediatric patients indicates that endocrinopathies peak within 2 years of the initial TBI, were more prevalent in females, and were predominantly reported as precocious sexual development (79). In the geriatric population, non-survivors of TBI were more likely to be males (80).…”
Section: Sensory Hypersensitivity and Estrous Cyclicitymentioning
confidence: 99%
“…In juvenile and aging TBI research, women and female rodents would not be actively cycling, thereby having lower circulating gonadal hormones levels, where post-menopausal women have been indicated to respond similar to males (78). However, an epidemiological study of TBI in pediatric patients indicates that endocrinopathies peak within 2 years of the initial TBI, were more prevalent in females, and were predominantly reported as precocious sexual development (79). In the geriatric population, non-survivors of TBI were more likely to be males (80).…”
Section: Sensory Hypersensitivity and Estrous Cyclicitymentioning
confidence: 99%
“…Hypopituitarism is a long-term complication of TBI in pediatric patients, 72 and pituitary deficiencies have been reported following moderate-severe and mild injuries. [72][73][74] We recently demonstrated that pediatric patients with a TBI have 3.22 times the risk of a subsequent central endocrinopathy compared with the general pediatric population. 74 Aging may also represent a critical period of vulnerability, given senescence is a risk factor for the development of post-traumatic hypopituitarism.…”
Section: Discussionmentioning
confidence: 99%
“…[72][73][74] We recently demonstrated that pediatric patients with a TBI have 3.22 times the risk of a subsequent central endocrinopathy compared with the general pediatric population. 74 Aging may also represent a critical period of vulnerability, given senescence is a risk factor for the development of post-traumatic hypopituitarism. 75 Future studies should include juvenile and aged rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear is whether those with acute deficiencies continue to have chronic deficiencies or whether those with chronic deficiencies develop them over time. However, pediatric TBI are 3 times more likely to have a central endocrine diagnosis compared to the uninjured population (137). Despite the necessity of proper pituitary function for normal physical and brain development, hypopituitarism continues to go unrecognized and untreated in children following TBI.…”
Section: Hormonalmentioning
confidence: 99%